Researching the Tutor in Online Practice: Reflections on an appropriate research methodology - McConlogue, Teresa; Bowskill, Nick (Proceedings of the International Conference on Networked Learning, 2002)
This paper, describes the research methodology used in a study on an online tutor’s educational beliefs. It describes the methods used in the study and discusses their appropriacy. It presents both the researcher’s and the participant’s interpretation of the case study data and comments on them. The conclusion reached was that the research experience was of mutual benefit to both parties. It was agreed that the humanistic style of research, which respected the views of both parties and, to some extent, shared decision-making about the direction of the research and the methods used, was an important feature. Moreover, it was agreed that reading the other’s interpretation was helpful in gaining new insights into the data. Finally it was concluded that the methods used could be developed in a future study where the research would continue in a more equitable way with researcher and participant in conversation exploring each other’s practice.